1999
DOI: 10.1021/jp991856x
|View full text |Cite
|
Sign up to set email alerts
|

XPS Study of Nitrided Molybdena/Titania Catalyst for the Hydrodesulfurization of Dibenzothiophene

Abstract: The relationship between the molybdenum species of nitrided Mo/TiO2 catalysts and the HDS activity of the catalysts was studied by XPS and X-ray diffraction. The HDS of dibenzothiophene was carried out in a fixed-bed microreactor at 573 K and 10.1 MPa of total pressure. The 10.3% MoO3/TiO2 catalyst was nitrided by a temperature-programmed reaction with ammonia at 4 L h-1 at various temperatures. The 1023 K nitrided catalyst held the highest TOF (based on CO adsorption). From XPS analysis, it was found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…The superior activity of Mo 2 N/Al 2 O 3 compared with sulfided NiMo/Al 2 O 3 was observed by Colling and Thompson (319,344) for the HDN of PY. The HYD activity was enhanced significantly in the presence of H 2 S (186), in agreement with Nagai et al (347). Aromatics were predominant hydrocarbons in both studies.…”
Section: Vi2123 Effect Of H 2 S On Stability Of Mo Nitridesupporting
confidence: 90%
See 1 more Smart Citation
“…The superior activity of Mo 2 N/Al 2 O 3 compared with sulfided NiMo/Al 2 O 3 was observed by Colling and Thompson (319,344) for the HDN of PY. The HYD activity was enhanced significantly in the presence of H 2 S (186), in agreement with Nagai et al (347). Aromatics were predominant hydrocarbons in both studies.…”
Section: Vi2123 Effect Of H 2 S On Stability Of Mo Nitridesupporting
confidence: 90%
“…In the study on the HDS of DBT over nitrided Mo/Al 2 O 3 in the absence of N-compounds, Nagai et al (346,347) observed that nitrogen in the nitride phase was exchanged with the sulfur from the feed. In the study on the HDS of DBT over nitrided Mo/Al 2 O 3 in the absence of N-compounds, Nagai et al (346,347) observed that nitrogen in the nitride phase was exchanged with the sulfur from the feed.…”
Section: Vi2123 Effect Of H 2 S On Stability Of Mo Nitridementioning
confidence: 99%
“…The N1s peak at 393.3 eV in the spectrum acquired at the sample particle surface indicates the formation of TiN x O y . 37 At depths of 15 to 115 nm, an N1s peak of 396.9 eV is exhibited in the spectra, resulting either from the formation of Ti-N bonds 43,44 or the presence of interstitial nitrogen in a titanium-nitrogen solid solution, 44 as seen at depths of 15 to 30 nm and 45 to 115 nm, respectively, in the spectra of Fig. 7.…”
Section: Paper Pccpmentioning
confidence: 95%
“…At depths of 15 and 30 nm, peaks appeared at 460.5 (Ti2p 1/2 ) and 454.7 eV (Ti2p 3/2 ), which are attributed to the formation of Ti-N bonds. 43 From 45 to 115 nm, the Ti2p 1/2 and Ti2p 3/2 peaks shift to lower binding energies with increasing depth. In addition, peaks at 459.7 and 453.6 eV, corresponding to metallic titanium, are observed at depths greater than 130 nm.…”
Section: Paper Pccpmentioning
confidence: 96%
“…The nitrided 6.6 wt% Mo/Al 2 O 3 catalyst exhibited the highest CO adsorption per surface Mo atom. Nagai et al [74,75] reported that the irreversible CO uptakes of the 973 Knitrided 12.5% Mo/Al 2 O 3 and 10.3% Mo/TiO 2 were 0.99 9 10 -2 and 3.63 9 10 -2 molecules/nm 2 , respectively. These values were approximately two orders of magnitude lower than the values obtained by other researchers; i.e., 2.6 molecules/nm 2 for 835 K-nitrided cMo 2 N [35] and 1.18 for c-Mo 2 N. The CO adsorption for molybdenum nitride was estimated to be 11 molecules/nm 2 [76], assuming that one molecule of CO is irreversibly chemisorbed per every four Mo metal atoms in Mo 2 N. These results suggest that the experimental CO adsorption could be misleading because of multiple adsorption of CO on the Mo atoms binding of nitrogen to the Mo in the nitride.…”
Section: Surface Propertiesmentioning
confidence: 99%